Isolation of a novel LPS-induced component of the ML superfamily in Ciona intestinalis. Issue 1 (November 2015) - Vizzini, Aiti; Bonura, Angela; Longo, Valeria; Sanfratello, Maria Antonietta; Parrinello, Daniela; Cammarata, Matteo; Colombo, Paolo
Abstract ML superfamily represents a group of proteins playing important roles in lipid metabolism and innate immune response. In this study, we report the identification of the first component of the ML superfamily in the invertebrate Ciona intestinalis by means of a subtractive hybridization strategy. Sequence homology and phylogenetic analysis showed that this protein forms a specific clade with vertebrate components of the Niemann-Pick type C2 protein and, for this reason, it has been named Ci-NPC2. The putative Ci-NPC2 is a 150 amino acids long protein with a short signal peptide, seven cysteine residues, three putative lipid binding site and a three-dimensional model showing a characteristic β-strand structure. Gene expression analysis demonstrated that the Ci-NPC2 protein is positively upregulated after LPS inoculum with a peak of expression 1 h after challenge. Finally, in-situ hybridization demonstrated that the Ci-NPC2 protein is preferentially expressed in hemocytes inside the vessel lumen.